2023
DOI: 10.1002/hsr2.1365
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to infection prevention and control measures and risk of exposure among health‐care workers: A cross‐sectional study from the early period of COVID‐19 pandemic in Addis Ababa, Ethiopia

Abel Weldetinsae,
Zinabu A. Alemu,
Kirubel Tefaye
et al.

Abstract: Background and Aim: Healthcare workers (HCWs) are considered a high-risk group for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure, ascribed to the amount of time they spend in health-care facilities (HCFs). This study aimed to assess HCWs' compliance with Infection Prevention and Control (IPC) procedures and the risk of exposure during the early period of the pandemic in Addis Ababa, Ethiopia. Methods: A descriptive cross-sectional survey was conducted from June to September 2020. With a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This amounted to only 22.5% of the total study population. 19 In another study carried out by Haas et al among 191 healthcare personnel, compliance to appropriate hand hygiene techniques was observed only 40 % of the time between visits to different patients of COVID-19. 20 The significance of COVID appropriate behavior and occurrence of breakthrough infections has been emphasized elaborately by a study done by Masthi R et al 21…”
Section: Discussionmentioning
confidence: 94%
“…This amounted to only 22.5% of the total study population. 19 In another study carried out by Haas et al among 191 healthcare personnel, compliance to appropriate hand hygiene techniques was observed only 40 % of the time between visits to different patients of COVID-19. 20 The significance of COVID appropriate behavior and occurrence of breakthrough infections has been emphasized elaborately by a study done by Masthi R et al 21…”
Section: Discussionmentioning
confidence: 94%
“…In Dammam, Saudi Arabia, 15 Healthcare providers (HCPs) preventive behavior was significantly higher among those with more knowledge of COVID-19, positive attitude, higher fear, and nursing profession (p=0.01). In Ethiopia, 9 HCWs who received training on IPC protocols and working in treatment centers had an increased attitude of following IPC standards by at least four times higher compared to those without training, while in Tanzania, 14 the identified predictors of HCWs' compliance with IPCSPs include years of work experience, having experienced a needlestick injury, and previous IPC training or an IPC seminar. Moreover, our study also noted that HCWs who have a recognized antimicrobial steward program team/unit or have antimicrobial stewardship standard policies and procedures at healthcare facilities, those who believe that the COVID-19 pandemic improves adherence to IPCs, those with evidence of immunity by documentation for vaccines, or by laboratory evidence of immunity, or by laboratory confirmation of disease were seen to have an increased IPC adherence.…”
Section: Discussionmentioning
confidence: 99%
“…8 In contrast, one study in Addis Ababa, Ethiopia, reported that COVID-19 pandemic did not improve the level of adherence to IPC procedures among HCWs. 9 It is reported that poor infection control measures were linked to SARS-CoV-2 seropositivity among HCWs during the second and third COVID-19 waves. 10 The study conducted in Al Riyadh, Saudi Arabia, uncovered that 80.2% of healthcare workers (HCWs) demonstrated good infection control practices in hospitals, a rate lower than estimates in other locations.…”
Section: Introductionmentioning
confidence: 99%
“…In several settings, the COVID-19 pandemic had a negative impact on the adherence of healthcare staff to infection control measures and on circulation of MDROs in the same settings. This is evident from several reports from a large number of countries [17][18][19][20][21][22][23][24]. As known, the strategies to prevent CLABSI are linked to correct insertion and maintenance of the device [25].…”
Section: Introductionmentioning
confidence: 99%